2020
DOI: 10.1007/s00374-020-01475-8
|View full text |Cite
|
Sign up to set email alerts
|

Catch crop diversity increases rhizosphere carbon input and soil microbial biomass

Abstract: Catch crops increase plant species richness in crop rotations, but are most often grown as pure stands. Here, we investigate the impacts of increasing plant diversity in catch crop rotations on rhizosphere C input and microbial utilization. Mustard (Sinapis alba L.) planted as a single cultivar was compared to diversified catch crop mixtures of four (Mix4) or 12 species (Mix12). We traced the C transfer from shoots to roots towards the soil microbial community and the soil respiration in a 13C pulse labelling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 52 publications
0
12
2
Order By: Relevance
“…Further, we found that flower strips with many different plant species and evenly distributed and more diverse plant populations had lower C sequestration rates. Thus, in contrast to a previous study showing that cover crop diversity may have a positive effect on C inputs (Gentsch et al 2020), the present study suggests a potential trade-off between C sequestration and plant species diversity in the flower strips.…”
Section: Uncertaintiescontrasting
confidence: 99%
“…Further, we found that flower strips with many different plant species and evenly distributed and more diverse plant populations had lower C sequestration rates. Thus, in contrast to a previous study showing that cover crop diversity may have a positive effect on C inputs (Gentsch et al 2020), the present study suggests a potential trade-off between C sequestration and plant species diversity in the flower strips.…”
Section: Uncertaintiescontrasting
confidence: 99%
“…Rhizodeposition during CC growth (root-derived C) is another important way that CC can add C to agroecosystems (Kuzyakov & Schneckenberger, 2004). In a pulse labeling experiment using fall-seeded CC, Gentsch et al (2020) concluded that diversified CC mixtures improve the efficiency of C cycling in cropping systems through greater atmospheric C uptake, transport rates towards the rhizosphere, microbial incorporation, and a prolonged residence time in the soil environment. Austin et al (2017) found that CC rhizodeposition accounted for 33% of total belowground C inputs of cereal rye.…”
Section: Soil C Storagementioning
confidence: 99%
“…Catch crop mixtures were shown to overyield the root biomass of pure stands and show higher potential for efficient soil exploration by roots (Heuermann et al, 2019). Increasing CC diversity also stimulates soil microbial diversity and biomass (Gentsch et al, 2020;Vukicevich et al, 2016), which represent a considerable reservoir for N during winter (Paul, 2007) and may contribute to N immobilization.…”
Section: Introductionmentioning
confidence: 99%